Berberine inhibits breast carcinoma proliferation and metastasis under hypoxic microenvironment involving gut microbiota and endogenous metabolites - Yanfang, Sun; Zhou, QianQian; Chen, Fangming; Gao, Xiaoyan; Yang, Linjun; Jin, Xiaoyan; Wink, Michael; Sharopov, Farukh S.; Sethi, Gautam (Pharmacological research, 2023)
A potential role of berberine, a benzyl isoquinoline alkaloid, in cancer therapy is apparent. Its underlying mechanisms of berberine against breast carcinoma under hypoxia have not been elucidated. We focused on the doubt how berberine restrains breast carcinoma under hypoxia in vitro and in vivo. A molecular analysis of the microbiome via 16 S rDNA gene sequencing of DNA from mouse faeces confirmed that the abundances and diversity of gut microbiota were significantly altered in 4T1/Luc mice with higher survival rate following berberine treatment. A metabolome analysis liquid chromatography-mass spectrometer/mass spectrometer (LC-MS/MS) revealed that berberine regulated various endogenous metabolites, especially L-palmitoylcarnitine. Furthermore, the cytotoxicity of berberine was investigated in MDA-MB-231, MCF-7, and 4T1 cells. In vitro to simulate under hypoxic environment, MTT assay showed that berberine inhibited the proliferation of MDA-MB-231, MCF-7, and 4T1 cells with IC50 values of 4.14 ± 0.35 μM, 26.53 ± 3.12 μM and 11.62 ± 1.44 μM, respectively. Wound healing and trans-well invasion studies revealed that berberine inhibited the invasion and migration of breast cancer cells. RT-qPCR analysis shed light that berberine reduced the expression of hypoxia-inducible factor-1α (HIF-1α) gene. Immunofluorescence and western blot demonstrated that berberine decreased the expression of E-cadherin and HIF-1α protein. Taken together, these results provide evidence that berberine efficiently suppresses breast carcinoma growth and metastasis in a hypoxic microenvironment, highlighting the potential of berberine as a promising anti-neoplastic agent to combat breast carcinoma.